A poesia-resistência de mulheres no Brasil contemporâneo: uma análise discursiva materialista de “as 29 poetas hoje” - Alvim, Liliane Rodrigues de Albuquerque (2023)
This research aimed to discursively analyze how social conflicts, mainly gender, in contemporary Brazil manifest themselves in poetry present in the work “As 29 Poetas Hoje”. Furthermore, the denunciation of these social fissures and the amplification and circulation of the otherness of the discourses of these women poets. It also aims at politicization, through criticality constructed from Materialist Discourse Analysis, a theory in which we subscribe and which underpins our work, theoretically and analytically, mainly based on the works of Michel Pêcheux (2014a, 2014b, 2015, 2019) and Louis Althusser (1980, 1985). In the methodological path, we carried out an intersectional approach to the work, in order to represent different strata of women in Brazilian society and from there we chose six poems that address social and gender problems. Subsequently, we carried out the analyzes in a qualitative and interpretative way, relating the poetic materialities to the corresponding discursive and ideological formations. We realize that it is violence, in different manifestations, that interconnects the different combative counter-discourses of these women, whose poems proved to be a linguistic means of struggle, resistance and denunciation of the violations to which they are subjected historically and even today under the capitalist perspective – patriarchal and sexist – of (re)production of the work of which they are essential gear.